Pengaruh Pengetahuan Akuntansi, Skala Usaha, dan Pendidikan terhadap Penggunaan Informasi Akuntansi pada UMKM Kecamatan Sewon - Kholifatun Rosidah; Endang Sri Utami (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the influence of accounting knowledge, business scale, and educational background on the use of accounting information among MSME actors in Sewon District, Bantul Regency, Special Region of Yogyakarta. A quantitative approach was applied using a survey method involving 70 MSME respondents as the research sample. The collected data were processed and analyzed using multiple linear regression with the assistance of Statistical Product and Service Solutions (SPSS) version 25. The findings reveal that accounting knowledge has a positive and significant effect on the use of accounting information, indicating that the better MSME owners understand accounting principles, the more effectively they utilize such information to support decision-making processes. Conversely, business scale shows a negative and significant effect, suggesting that larger business operations may face increased complexity that limits the optimal use of accounting information. Meanwhile, educational background demonstrates no significant influence, implying that practical accounting competence plays a more crucial role than formal education in determining how accounting information is utilized. These results emphasize the importance of improving accounting literacy among MSME owners to strengthen financial management practices, enhance the accuracy of record-keeping, and support sustainable regional economic development.